Legal Protection Of Women Victim Online Gender-Based Violence (KBGO) - Putra, Rengga Kusuma; Khasanah, Dian Ratu Ayu Uswatun; Karisma, Dian; Idris, Maulana Fahmi; Pongantung, Ronald Jolly (Faculty of Law, Universitas Pekalongan, 2024)
Violence today does not only occur in the real world, but with the development of internet technology, it opens up opportunities for perpetrators to commit acts of violence by utilizing the internet, known as online gender-based violence (GBV). KBGO is more vulnerable to women and children, which not only causes suffering for victims physically, psychologically and even economically. The rights of victims have been deprived and their interests have been harmed by the perpetrators, so victims really need legal protection so that their rights are restored and their interests can be protected. Legal protection for victims of violence is provided by considering the losses suffered by victims, namely in the form of material and immaterial losses. Legal protection for women victims of online gender-based violence (KBGO), not only imposes punishment on the perpetrators of violence in the form of imprisonment and/or fines, but also provides the rights of victims who have been deprived and whose interests have been harmed by the actions of the perpetrators. The punishment that can be imposed on the perpetrators of violence has been regulated in Law Number 12 of 2022, including in the provisions of Article 14 and Article 15, with imprisonment and/or fines, even restitution, imposition of additional punishment or measures in the form of rehabilitation for the perpetrators, as stipulated in Article 16 and Article 17 of Law Number 12 of 2022. For legal protection of the rights of victims of violence, among others, it is regulated in Article 66 to Article 70 of Law Number 12 of 2022, which includes the right to handling, the right to protection and the right to recovery.Keywords:KBGO, Legal Protection, Victims, Women